2010
DOI: 10.1007/s10535-010-0131-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photoperiod during growth of Chenopodium rubrum mother plants on properties of offspring

Abstract: Using in vitro culture, we determined the effect of photoperiod during growth of Chenopodium rubrum mother plants on vegetative and reproductive development of offspring. Photoperiod during flowering induction of mother plants (the first 6 d after the germination) has the key influence on seed germination and offspring growth, while offspring flowering and seed maturation is determined by photoperiod their mothers experienced during, and shortly after, flowering induction. The mechanism can be through changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…For instance, shade avoidance response in field corn contributes to crop competitiveness, particularly when combined with abiotic stresses (Page et al 2010a,b). The light environment is known to influence seed development in certain weed species (Brainard et al 2005;Mitrovic et al 2010), and perhaps also is important in wild-proso millet seed development. Alternatively, processes that influence resource capture (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, shade avoidance response in field corn contributes to crop competitiveness, particularly when combined with abiotic stresses (Page et al 2010a,b). The light environment is known to influence seed development in certain weed species (Brainard et al 2005;Mitrovic et al 2010), and perhaps also is important in wild-proso millet seed development. Alternatively, processes that influence resource capture (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanisms driving maternal environment-mediated differences in seed germinability include soil nutrients, temperature, photon flux density, photoperiod, and light spectral distribution (reviewed by: Roach and Wulff 1987;Gutterman 2000). Figueroa et al (2010) determined that maternal temperature effects on seed germinability of common groundsel (Senecio vulgaris L.) can occur during flower bud development, and Mitrovic et al (2010) found that maternal photoperiod effects on seed germinability of red goosefoot (Chenopodium rubrum L.) take place during the first 6 d of maternal plant growth. Thus, maternal environment effects on seed germinability potentially occur at any point during maternal plant growth and are species-specific.…”
Section: Resultsmentioning
confidence: 99%
“…Many publications have demonstrated that environmental experiences (e.g. light, nutrient, temperature, water,) of the maternal plant have influences on the performaces of the resulting progeny (Rossiter, 1996;Galloway, 2002;Etterson and Galloway, 2002;Galloway, 2005;Luzuriaga, et al, 2006;Galloway and Etteson, 2007;Uller, 2008;Wolf and Wade, 2009;Mitrovic, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%